Experimental visualization and characteristics of bubble nucleation during rapid decompression of supercritical and subcooled carbon dioxide. (February 2022) - Quinn, Declan; Stannard, Drew; Edwards, Jeff; Botros, Kamal K.; Johansen, Craig
Abstract: The rapid decompression of sub-cooled and supercritical carbon dioxide was investigated experimentally using schlieren and regular high-speed photography. An optically accessible expansion tube was designed and constructed. A test campaign with initial pressures ranging from 6.45–9.02 MPa and initial temperatures from 297–308 K was performed. High-speed schlieren imagery was used to visualize the decompression waves, evaporation waves, and an oscillatory phase change region present in the blowdown process. The time history of pressures at different locations along the expansion tube were recorded using fast response pressure transducers. Image and pressure signal analyses were performed to extract decompression wave speeds and evaporation wave speeds. Results were compared to analytical models and other experiments reported in the literature. The relationship between pressure undershoot and wave speed to the initial conditions was analysed. Highlights: Delayed Bubble Nucleation. Fracture Control of Pipelines Transporting Subcooled and Supercritical Carbon Dioxide. Schlieren Visualization. Rapid Decompression Characteristics of Subcooled and Supercritical Carbon Dioxide. Experimental Visualization of Rapid Decompression of Subcooled and Supercritical Carbon Dioxide.